Sotrovimab for Treatment of COVID-19 in Solid Organ Transplant Recipients. Issue 7 (15th April 2022) - Dhand, Abhay; Okumura, Kenji; Wolfe, Kevin; Lobo, Stephen A.; Nog, Rajat; Keller, Marina; Bodin, Roxana; Singh, Nandita; Levine, Avi; Nabors, Christopher
Abstract : Abstract :